Silymarin, the antioxidant component of Silybum marianum, protects against burn-induced oxidative skin injury - ERCAN, FERİHA; ŞENER, GÖKSEL; YÜKSEL, MERAL; AKBAY, TUĞBA (ELSEVIER SCI LTD, 2007)
Background: Despite recent advances, severe burn is one of the most common problems faced in the emergency room. Major thermal injury induces the activation of an inflammatory cascade resulting in local tissue damage, to contribute to the development of subsequent damage of multiple organs distant from the original burn wound. Objective: Silymarin, the major component of milk thistle has been shown to have antioxidant properties. In the present study, we investigated the putative antioxidant effect of local or systemic silymarin treatment on burn-induced oxidative tissue injury. Methods: Wistar albino rats were exposed to 90 degrees C bath for 10 s to induce burn. Silymarin either locally (30 mg/kg) applied on 4 cm(2) area or locally + systemically (50 mg/kg, p.o.) was administered after the burn and repeated twice daily. Rats were decapitated 48 h after injury and blood was collected for tumor necrosis factor-a (TNF-alpha) and lactate dehydrogenase (LDH) activity. In skin tissue samples malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity, and luminol-lucigenin chemiluminescense (CL) were measured in addition to the histological evaluation. Results: Burn caused a significant increase in TNF-a and LDH levels. MDA levels were increased and GSH levels were decreased in the skin at 48 h after-burn. Both local and systemic silymarin treatments significantly reversed these parameters. The raised MPO activity and luminol-lucigenin CL were also significantly decreased. Conclusion: Results indicate that both systemic and local administration of silymarin was effective against burn-induced oxidative damage and morphological alterations in rat skin. Therefore, silymarin merits consideration as a therapeutic agent in the treatment of burns. (C) 2006 Elsevier Ltd and ISBI. All rights reserved.
Keywords: Silymarin; burn skin; thermal; oxidative; injury; THERMAL-INJURY; ORGAN DAMAGE; RAT MODEL; LIPID-PEROXIDATION; REACTIVE OXYGEN; STRESS; INHIBITION; MELATONIN; BLOOD; STAGE